INFLUENCE OF SYMMETRIC AND ASYMMETRIC MACHINING STRATEGIES ON SURFACE ROUGHNESS IN FACE MILLING PROCESS OF COBALT-BASED SUPERALLOY - Bagci, E.; Aykut, S. (SCIBULCOM LTD, 2013)
In this work, the influence of symmetric and asymmetric milling approaches on surface roughness was investigated for face milling process of cobalt-based superalloy (Stellite 6) with PVD-coated tool using statistical methods. Cobalt-based superalloy is widely used in airplane and space industries and resistant to high temperature and corrosion. Face milling tests of cobalt-based superalloy were performed to investigate cutting speed, feed rate and cutting depth on surface roughness under dry cutting conditions. The settings of milling parameters were determined by using the experimental design method. The analysis of variance (ANOVA) was employed to analyse the effect of face milling parameters and milling approaches. The objective was to establish a model using multiple regression analysis between cutting speed, depth of cut, and feed rate with the surface roughness for symmetric and asymmetric milling processes of Stellite 6. Symmetric and asymmetric milling processes were compared by using average surface roughness as a function of feed rate, cutting speed and cutting depth.
Keywords: asymmetric and symmetric milling; cobalt-based superalloy; surface roughness; ANOVA; TOOL-LIFE; MICROSTRUCTURE; PREDICTION; DESIGN; WEAR; Engineering